“God is real”: Narratives of religiously motivated desistance - DiPietro, Stephanie M. (Criminology, 2021)
This study examines the role of Islam in shaping processes of criminal desistance among four men, each with extensive histories of crime and violence. The men's life histories are unique, first, in that they came of age in contexts of extreme violence and religious persecution—all men are Muslim and were children during the ethnic cleansing campaigns in Bosnia in the early 1990s—and second, in that they all identify their newfound or newly cemented dedication to Islam as the primary catalyst for their desistance. Thematic analyses rooted in the principles of grounded theory reveal some consistencies with extant research on religiously motivated desistance, including the role of faith as a means for self-transformation and behavioral guidance. They also shed light on traditionally understudied mechanisms in the faith-desistance relationship, including the power of religion to reconfigure masculine identities, to reconcile with traumatic pasts, and to cultivate a new moral universe. In examining these men's life histories, we make the case for considering the transformative benefits of Islam in studies of crime and desistance, and for disentangling the role of distinctive faith factors (e.g., faith and religious participation) in processes of change.